Detection of Fraud Through Professional Scepticism - Nugrahanti, Trinandari Prasetyo; Siladjaja, Muljanjo; Fardiman, Fardiman; Rita, Henny; Ashari, Hasan (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose – This study aims to determine the factors influencing the auditor's ability to detect fraud through professional scepticism. Methodology/approach – This research method is quantitative and descriptive. The primary data collection technique uses a questionnaire distributed to the supervisory auditors of central government agencies working at the Central BPKP in the DKI Jakarta Region, Indonesia. Sampling using the purposive sampling method obtained several 40 respondents. Data analysis tools use multiple linear regression analysis and path analysis. Findings – The results showed that the auditor's competence and the internal control system positively affected professional skepticism, but workload did not affect professional skepticism. Meanwhile, professional skepticism has a significant positive impact on the auditor's ability to detect fraud. Novelty/value – The existence of an attitude of professional skepticism will be better able to analyze fraudulent acts in the financial statements so that the auditor will increase the detection of fraud in the next auditing process.